1998
DOI: 10.1097/00005650-199805000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the NIH Consensus Conference on Helicobacter Pylori on Physician Prescribing Among a Medicaid Population

Abstract: Two years after the highly publicized NIH conference on the eradication of Helicobacter pylori, antimicrobial agents were not widely prescribed among the Pennsylvania Medicaid population. In treating this underserved population, physicians do not appear to be using recommendations developed by an NIH expert panel based on recent scientific advances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 45 publications
1
17
1
1
Order By: Relevance
“…Many ulcer patients even today are still being treated with chronic or on demand acid suppressants, a therapy now considered obsolete 1112 Vreeburg et al showed that only a minority of patients admitted with an upper gastrointestinal bleed in the Amsterdam area was tested for the presence of H pylori , and few were actually offered appropriate treatment 13. Similar disturbing data were published from the USA12 14-16 and the UK 17.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Many ulcer patients even today are still being treated with chronic or on demand acid suppressants, a therapy now considered obsolete 1112 Vreeburg et al showed that only a minority of patients admitted with an upper gastrointestinal bleed in the Amsterdam area was tested for the presence of H pylori , and few were actually offered appropriate treatment 13. Similar disturbing data were published from the USA12 14-16 and the UK 17.…”
supporting
confidence: 79%
“…12 Vreeburg et al showed that only a minority of patients admitted with an upper gastrointestinal bleed in the Amsterdam area was tested for the presence of H pylori , and few were actually offered appropriate treatment 13. Similar disturbing data were published from the USA12 14-16 and the UK 17. But even if the right patients are treated, surveys have shown that many different inappropriate and ineffective treatments are being used 16-19.…”
mentioning
confidence: 99%
“…However, a study examining prescribing habits for Medicaid patients after the statement's release showed that although use of antibiotics rose for this condition (from 6.5 percent to 10.2 percent), physicians continued to use traditional and ineffective H2-receptor antagonists as their preferred approach for 72 percent of all patients. 7 The Cox-2 arthritis medications provide a final illustration of inappropriate use of medications. These heavily promoted drugs are popular because of their presumed decrease in stomach ulcers, a complication of long-term treatment with the standard nonsteroidal arthritis therapy.…”
Section: Prescription-related Deaths Far Outnumber Other Accidental Dmentioning
confidence: 99%
“…1 At the 1994 NIH (National Institutes of Health) Consensus Conference on the medical treatment of ulcer, the optimal treatment of ulcer was defined as combination therapy consisting of PPIs or histamine 2 -receptor blockers and broad-spectrum antibiotics; prescribing patterns have been changed in many communities, as a direct result, although there is still substantial room for improvement in some communities. 8 These discoveries have had a revolutionary effect on the previous concepts about acid secretion and ulcers. Previously, vagus nerve hyperactivity had been defined as a cause of increased acid secretion following the work of Dragstedt and others at the University of Chicago, Chicago, Ill, who demonstrated that patients with ulcers typically secreted acid continuously, as opposed to the "normal" triphasic pattern (cephalic, gastric, and intestinal phases) of secretion.…”
Section: Medical Treatment Since 1985: Antibiotics Become An Importanmentioning
confidence: 99%
“…17 Whether more uniform application of the latest treatments can improve these results is unknown. 8,17,22 …”
Section: Has the Incidence Of Ulcer Changed?mentioning
confidence: 99%